Status of Recombinant Factor VIII Concentrate Treatment for Hemophilia A in Italy: Characteristics and Clinical Benefits - Schiavoni, Mario; Napolitano, Mariasanta; Giuffrida, Gaetano; Coluccia, Antonella; Siragusa, Sergio; Calafiore, Valeria; Lassandro, Giuseppe; Giordano, Paola (Frontiers in Medicine, 2019)
Currently there is a great interest towards recombinant factor VIII (rFVIII) products that have technological solutions to prolong their half-life and to reduce the risk of alloantibodies against FVIII (inhibitors). At the present the Italian Health Care System offers a wide range of rFVIII concentrates belonging to the first generation as well as to the third generation, some of which with peculiar pharmacodinamic and pharmacocinetic (PK) prophiles, up to an extended half-life (EHL) product. The first generation full-length rFVIII (FL-rFVIII) octocog alfa (Recombinate® Baxter/BIOVIIIx), although is the oldiest rFVIII product, has some features that make it quite current. To the third generation products belong two modified rFVIII octocog alfa molecules (Advate®-Shire and Kovaltry®-Bayer), followed by B domain deleted rFVIII (BDD-rFVIII) moroctocog alfa (ReFacto®-Pfizer), B domain truncated (BDT-rFVIII) turoctocog alfa (NovoEight®, Novo Nordisk), BDD-rFVIII simoctocog alfa (Nuwiq®, Kedrion), single-chain BDT-rVIII lonoctocog alfa (Afstyla®- CSL Behring) and BDD-rFVIIIFc efmoroctocog alfa (Elocta®, Sobi-Biogen). Turoctocog alfa, simoctocog alfa and lonoctocog alfa may be considered innovative products. Their high affinity to von Willebrand factor (vWF) helps to reduce renal clearance and to prolong someway half-life. Efmoroctocog alfa, a first-in-class rFVIII-Fc fusion protein (rFVIIIFc) belongs to EHL products with a half life 1.5 times longer than that of conventional plasma-derived FVIII (pd-rFVIII) and rFVIII products. All this concentrates have been shown their efficacy, safety and immunogenecity in clinical studies both on previous treated patients (PTPs) and on previous untreated ones (PUPs).This review considers the commercially available rFVIII products in Italy indicated for treatment of patients with severe hemophilia A (HA), highlighting their PK characteristics, immunogenicity and benefits from a clinical point of view.